Concurrent epidemics of influenza A/H3N2 and A/H1N1pdm in Southern China: A serial cross-sectional study. Issue 3 (March 2016) - Wu, Chunli; Wang, Maggie Haitian; Lu, Xing; Chong, Ka Chun; He, Jason; Yau, Chun-Yip; Hui, Mark; Cheng, Xiaowen; Yang, Li; Zee, Benny Chung-Ying; Zhang, Renli; He, Ming-Liang
Summary: Objectives: This study aimed to elucidate the antibody response pattern of multiple influenza subtypes through a 4-year serological study of a general population in Shenzhen, Southern China. Methods: A serial cross-sectional serological survey was conducted at eight time points between 2009 and 2012. A total number of 5876 subjects were recruited from all age groups. The influenza subtypes tested were A/H1N1, A/H3N2, B/Yamagata, B/Victoria, and A/H1N1pdm. Genetic sequencing and phylogenetic analysis were performed on 127 H3 genes and 28 H1pdm genes. Results: We found concurrent epidemics of A/H3N2 and A/H1N1pdm with simultaneous peak times at March 2011. A/H3N2 was the dominant subtype. Ten residue substitutions (S61N, T64I, K78E, K160N, N161S, A214S, T228A, A229V, V239I, N294K, and N328S) were found in the H3 gene that might underlie its epidemic. The elderly group showed an antibody response cycle that was weaker in magnitude and slower in peak time than in younger groups. Conclusions: The study provides a broad transmission picture and epidemiological characteristics of the major flu subtypes. The findings suggest that it may be necessary to include the A/H1N1pdm strain to the current trivalent or quadrivalent vaccine design. The delayed antibody response cycle in the elderly group indicates the need for better protection of elderly people that might be achieved by an earlier vaccination at a higher dose.